2018
DOI: 10.1177/1747021818772045
|View full text |Cite
|
Sign up to set email alerts
|

Moral fatigue: The effects of cognitive fatigue on moral reasoning

Abstract: We report two experiments that show a moral fatigue effect: participants who are fatigued after they have carried out a tiring cognitive task make different moral judgements compared to participants who are not fatigued. Fatigued participants tend to judge that a moral violation is less permissible even though it would have a beneficial effect, such as killing one person to save the lives of five others. The moral fatigue effect occurs when people make a judgement that focuses on the harmful action, killing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 100 publications
(122 reference statements)
1
31
0
Order By: Relevance
“…In doing so, they found that participants in the hard-to-read-font condition are more likely to endorse utilitarian judgments. Timmons and Byrne (2018) used an ego-depletion task similar to the e-crossing task and found that depleted participants tend to be more deontological than non-depleted ones. Bago and De Neys (2018) implemented a tworesponse paradigm and, using several sacrificial dilemmas, found that about 70% of the utilitarian deliberative choices were already utilitarian under intuition.…”
Section: Ousmentioning
confidence: 99%
“…In doing so, they found that participants in the hard-to-read-font condition are more likely to endorse utilitarian judgments. Timmons and Byrne (2018) used an ego-depletion task similar to the e-crossing task and found that depleted participants tend to be more deontological than non-depleted ones. Bago and De Neys (2018) implemented a tworesponse paradigm and, using several sacrificial dilemmas, found that about 70% of the utilitarian deliberative choices were already utilitarian under intuition.…”
Section: Ousmentioning
confidence: 99%
“…In doing so, they found that participants in the hard-to-read-font condition were more likely to endorse utilitarian judgments in sacrificial dilemmas. Timmons and Byrne (2018) used an ego-depletion task similar to the e-crossing task and found that depleted participants tended to be more deontological than non-depleted ones in sacrificial moral dilemmas.…”
Section: Review Of the Empirical Evidencementioning
confidence: 99%
“…Load reduces utilitarian judgments, while leaving deontological judgments unaffected Conceptual primes studies Valdesolo & DeSteno (2006) Sacrificial dilemmas Affect induction increases deontological choices Kvaran et al (2013) Sacrificial dilemmas Emotional prime increases deontological choices Analytical prime increases utilitarian choices Spears et al (2018) Sacrificial dilemmas Attention prime increases utilitarian choices Capraro et al (2019) Oxford Utilitarianism Scale Priming intuition increases non-utilitarian judgments in the instrumental harm dimension, but not in the impartial beneficence dimension Ego depletion studies Trémolière et al (2012) Sacrificial dilemmas Depletion increases deontological choices Timmons & Byrne (2018) Sacrificial dilemmas Depletion increases deontological choices…”
Section: Utilitarian Judgments Dependent Variablementioning
confidence: 99%
“…MJAC assumes that moral judgments are dynamical and context-dependent, and as such it is the approach that is best positioned to understand the diverse contextual influences on moral judgment. It is beyond the scope of the current paper to describe and account for all the known contextual influences on moral judgment (e.g., an incomplete list would include: Bostyn et al(e.g., an incomplete list would include: Bostyn et al, 2018;Christensen et al, 2014;Christensen & Gomila, 2012;Costa et al, 2014;Cushman et al, 2012;Everett et al, 2016Everett et al, , 2018Forbes, 2018;Francis et al, 2016Francis et al, , 2017Lee & Holyoak, 2020;Petrinovich & O'Neill, 1996;Rozin et al, 1999Rozin et al, , 2008Schein, 2020;Timmons & Byrne, 2019;Uhlmann et al, 2015;Valdesolo & DeSteno, 2006;Vasquez et al, 2001;Vasudev & Hummel, 1987). However, MJAC predicts understanding these diverse context effects depends on (a) accounting the learning history (e.g., in the cases of emotional influences and the foreign language effect) and, (b)…”
Section: Emotion Effectsmentioning
confidence: 99%